Electrical activation of boron coimplanted with carbon in a silicon substrate - Souza, Joel Pereira de (2014)
It is demonstratedt hat the electrical activation in B+ (5.0X 1014 cm-² at 50 keV) implanted Si samples submitted to furnace annealing can be noticeably affected by a C+ coimplantation. It was found that a C+ dose ten times lower than that of B+ is not sufficient to influence the activation behavior of B. However, C+ implanted to a dose equal to or ten times higher than the B+ dose contributed, respectively, to the reduction or enhancement of the electrical activation of B after annealing in the temperature range of 450-700 °C. In addition, the reverse annealing of B is attenuated in the coimplanted samples and suppressed in samples where the C+ implantation damage was annealed prior to the B+ implantation. At temperatures > 700 °C the electrical activation is not significantly affected by the C+ coimplantation. A model considering interaction between C and Si self-interstitial atoms during thermal annealing is proposed to account for the activation behavior of B in the dually implanted samples.